6(2-t)-(4-4t)=5

Simple and best practice solution for 6(2-t)-(4-4t)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2-t)-(4-4t)=5 equation:


Simplifying
6(2 + -1t) + -1(4 + -4t) = 5
(2 * 6 + -1t * 6) + -1(4 + -4t) = 5
(12 + -6t) + -1(4 + -4t) = 5
12 + -6t + (4 * -1 + -4t * -1) = 5
12 + -6t + (-4 + 4t) = 5

Reorder the terms:
12 + -4 + -6t + 4t = 5

Combine like terms: 12 + -4 = 8
8 + -6t + 4t = 5

Combine like terms: -6t + 4t = -2t
8 + -2t = 5

Solving
8 + -2t = 5

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -2t = 5 + -8

Combine like terms: 8 + -8 = 0
0 + -2t = 5 + -8
-2t = 5 + -8

Combine like terms: 5 + -8 = -3
-2t = -3

Divide each side by '-2'.
t = 1.5

Simplifying
t = 1.5

See similar equations:

| 4(3-t)-(2-2t)=7 | | 9.8+x/5=10.4 | | 7x=5y | | y(3y+8)=-5 | | (r/-7)-5=-6 | | 3x+4=(x-8) | | 2y+8=10y | | w^2-14w-72=0 | | c=5(F-32)/9 | | 60x^2-44x-5= | | -24+6=-5 | | -10x-3x-3x=-70 | | (3x-6)(5x-9)= | | 3x/4-1 | | 2x^3=35 | | x+2x+x+27=167 | | -630=76x+126y | | 7.5+0.5x=3/4x | | 3r^2+r-24=0 | | 9x+2y=36 | | 4t^2-3t-5=0 | | -8x-7x=64 | | 5x-10+5x=-10 | | 5x-3=3x-11 | | -3x-7y=21 | | x+x^2=x^3 | | (9-2x)2=0 | | 8y+9x=36 | | -3x+5=11 | | 0.5(x+2)=0.1+3(0.1+0.3) | | in(7x+4)=1 | | 1/4+1/13-1/52 |

Equations solver categories